The more academic burnout students got, the more problematic mobile phone use they suffered? A meta-analysis of mainland Chinese adolescents and young adults - Li, Shunyu; Xu, Mengmeng; Zhang, Yuxuan; Wang, Xiaotong (Frontiers in Psychology, 2023)
In recent years, the relationship between academic burnout (AB) and problematic mobile phone use (PMPU) has become the hot issue of scholars, and a lot of related research has been carried out, but the results are different. Most studies showed that there was a significant positive correlation between AB and PMPU. However, some studies showed that the relationship between AB and PMPU was not significant. While this study aimed at exploring the relationship between AB and PMPU, as well as the influence of some mediators (region, age, gender, publication year, the measurement instrument) on them. According to the searching process for studies of PRISMA, we searched the related studies on AB and PMPU in Mainland China from January 2012 to November 2022 from CNKI, Wanfang Data, Chongqing VIP Information Co., Ltd. (VIP), Baidu scholar, ProQuest dissertations, Taylor & Francis, Springer, Web of Science, Google Scholar, EBSCO and PsyclNFO. Eventually, 50 studies were included in the meta-analysis, involving 38488 subjects, with the sample size ranging from 193 to 2260. CMA 3.0 was used to analyse the overall effect and test the moderating effect. The result shows that the relationship between AB and PMPU can be considered as a moderate correlation (r=.414, 95%CI [.384, .443]), and Meta-regression shows that the relationship between AB and PMPU was moderated by the measurement instrument and publication year. Specifically, when the Mobile Phone Addiction Tendency Scale and the Smartphone Addiction Scale for College Students were used as PMPU measurement tools, the correlation coefficients between AB and PMPU were higher. When the publication year was used as a moderating variable, the relationship between AB and PMPU increased over the years. Systematic review registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022347277, PROSPERO CRD42022347277.